Active Compounds Of Ethyl Acetate Extract Of Stylotella Sp. Sponges From Selayar Islands Against Mcf-7 Breast Cancer Cells - Ilyas, Asriani; Hamzah, Sahyuni; Firnanelty, Firnanelty; Andriani, Titik (Al-Kimia, 2020)
Stylotella sp. sponge is a type of marine invertebrate animals that are widely distributed in Indonesian marine areas. One of the spreading areas of the Stylotella sp. sponge is in the Selayar Islands, South Sulawesi, Indonesia. Sponges have potential as a drug because they contain secondary metabolites. The aim study was to identify the types of secondary metabolite compounds and determine the bioactivity of Stylotella sp. compounds against MCF-7 breast cancer cells. The extraction method was used in the process of obtaining isolates because it is easy and economical. Testing the level of purity of isolates was carried out with three eluent systems which showed a single stain result. FTIR characterization results showed that pure isolates contained alkaloids which were characterized by the appearance of O-H, C-N, and C-H groups. The activity of MCF-7 cells using the colorimetric method showed an IC50 value of 14987.50 µg / mL, not toxic.